The PENGARUH KONSENTRASI PELARUT TERHADAP JUMLAH RENDEMEN DAN PROFIL KLT EKSTRAK DAUN KUMIS KUCING (Orthosiphon stamineus Benth) VARIETAS ORSINA-1 AGRIBUN PADA KONDISI OPTIMASI - Fauziah; Chaidir; M. Hanafi; Gusmaini (Jurnal Buana Farma, 2024)
Orsina-1 agribun variety of cat's whiskers (Orthosiphon stamineus O1A) is a superior variety with an environment-specific genotype, and provides high average wet and dry weight results when planted in lowland and medium areas. The purpose of this study was to examine the effect of solvent concentration on the amount of yield and TLC profile of cat's whiskers leaf extract (Orthosiphon stamineus Benth) variety of orsina-1 agribun under optimization conditions. In this study, optimization of extraction conditions was carried out by determining the ratio of powder to solvent and extraction time that gave the highest amount of yield using the maceration method. To determine the effect of solvent concentration on the amount of yield and TLC profile, O1A cat's whiskers leaf extract was macerated under optimization conditions using ethanol solvents 96%, 70%, 50%, 30% and water (ethanol 0%). Anova was applied and the significant effect of factors was tested at 95% confidence intervals. The results of the study showed that differences in extraction concentrations affected the yield of ethanol extract under optimization conditions (p-value = 0.000-0.001, p-value < α).